TB: Barrier in access, diagnosis and treatment completion - Marahatta, Sujan B.; Shrestha, Ashish; Bhattarai, Pramod R; Thapa, Anil; Lamichinnae, Bikash; Chhetri, Charu (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Tuberculosis (TB) is a major public health concern for Nepal like many other developing countries around the world. Economic barrier is one of the major problems in poor and marginalized population. Poor people mostly remain unaware of the treatment facilities and some find it difficult in seeking T.B treatment as they don’t trust the program and most of them don’t possess enough knowledge about the disease itself. Population residing in the remote areas of the countries can’t access the treatment facilities due to far distance of health facilities from there residence due to lack of roads and lack of transport. Thus difficult geography primarily in rural areas in the country acts as a barrier to access the health facility. TB infection faces add-on challenge with the advent of co-infection and possibility of increase in drug resistant TB. This is why detecting TB in its early stage would pose a number of advantages to the patient that would in turn help for early treatment. However, the challenges and barriers in early diagnosis remain that is being contributed by multifaceted factors. The lack of knowledge coupled with poor financial capacity to pay for the diagnosis especially in rural population prevents them from being diagnosed properly as well. Factors for not completing the treatment are when patient starts feeling better, lack of drugs, major side effects of the drugs and inadequate knowledge about advantages of completion of the drug treatment. The attitude of the hospital staff also in many cases leads to discontinuation of the treatment. Patient who have limited income and got financial support from their relatives explained about treatment going above their obtainable resources leading to early withdrawal from the treatment completion. Geography is one of the important issues for treatment completion as routine drug administration follow up in patient (farther from particular distance) is difficult and leads to exhaustion and withdrawal from the treatment.Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.76-80